Tailored topotactic chemistry unlocks heterostructures of magnetic intercalation compounds - Husremović, Samra; Gonzalez, Oscar; Goodge, Berit H.; Xie, Lilia S.; Kong, Zhizhi; Zhang, Wanlin; Ryu, Sae Hee; Ribet, Stephanie M.; Fender, Shannon S.; Bustillo, Karen C.; Song, Chengyu; Ciston, Jim; et al. (Nature communications, 2025)
The construction of thin film heterostructures has been a widely successful archetype for fabricating materials with emergent physical properties. This strategy is of particular importance for the design of multilayer magnetic architectures in which direct interfacial spin-spin interactions between magnetic phases in dissimilar layers lead to emergent and controllable magnetic behavior. However, crystallographic incommensurability and atomic-scale interfacial disorder can severely limit the types of materials amenable to this strategy, as well as the performance of these systems. Here, we demonstrate a method for synthesizing heterostructures comprising magnetic intercalation compounds of transition metal dichalcogenides (TMDs), through directed topotactic reaction of the TMD with a metal oxide. The mechanism of the intercalation reaction enables thermally initiated intercalation of the TMD from lithographically patterned oxide films, giving access to a family of multi-component magnetic architectures through the combination of deterministic van der Waals assembly and directed intercalation chemistry. Synthesis of heterostructures of magnetic intercalation compounds in transition metal dichalcogenides (TMDs) via directed topotactic reactions enables the creation of multi-component magnetic architectures, overcoming limitations of crystallographic incommensurability